Effects of different types of exercise intensities on immune responses, bone metabolism markers, antioxidant status and selected physiological parameters in physically inactive adults - Suhaimi, Muhammad Zuhaili (2025)
High-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) was proven to enhance general fitness and health in healthy individuals. However, to date, studies on the effects of HIIT and MICT on immune responses, bone metabolism markers and antioxidant status in physically inactive adults are still limited. Therefore, the study was carried out. Thirty-six physically inactive male and female adults, aged 18-35 years were recruited and randomly assigned to HIIT, MICT or control groups with 12 participants per group (n=12). Participants in the HIIT group performed 2 sets of 6-8 repetitions of running at 85- 95% of HRmax on a motorised treadmill for 30 seconds, 3 times per week for 8 weeks. Participants in the MICT group performed 30 min of running on a motorised treadmill at 55-70% of HRmax, 3 times per week for 8 weeks. Participants in the control group did not engage in any exercise training throughout the intervention period. Anthropometric measurements, maximum oxygen consumption (VO2max), Wingate anaerobic capacity, isokinetic muscular strength and power, blood (for the analysis of whole blood count, calcium, alkaline phosphatase, osteocalcin, carboxy-terminal telopeptide of type-1 collagen and total antioxidant status) and saliva samples (for analysis of saliva flow rate and salivary lysozyme concentration and secretion rate) were taken prior to and following 8 weeks of training intervention. Results indicated that both HIIT and MICT significantly increased salivary lysozyme concentration and dominant knee extension average power at 300º.s-1 compared to pre-test measurement (p<0.05), though no significant differences were observed between groups (p>0.05). VO2max improved significantly in the HIIT group (p<0.05), whereas total monocyte count and serum ALP concentration were significantly higher in the MICT group compared to controls post-intervention (p<0.05). A significant reduction in anaerobic and peak power were noted in both groups at post-test compared to pre-test measurements (p<0.05). No significant differences across groups and time were found in the other measure parameters. In conclusion, both HIIT and MICT enhance specific immune response markers and isokinetic muscular power in physically inactive adults. However, HIIT demonstrated superior improvements in cardiovascular fitness and MICT was better at enhancing bone metabolism marker. These findings suggest that practitioners should consider incorporating HIIT into exercise regimens as a time- efficient alternative that may appeal to those with perceived time constrains for exercise while providing effective health benefits.